PEDAGOGICAL AND PSYCHOLOGICAL FUNDAMENTALS OF TEACHER PROFESSIONAL COMPETENCE (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The article focuses on pedagogical processes in the upgrading courses that are organized to develop and improve the professional competence of teachers. In addition, the author has identified the stages of professional development of the teacher and the development of their professional competence in teacher training